Distress of tertiary education students in Australia during the COVID‐19 pandemic. Issue 3 (3rd October 2022) - Tuck, David; Wiley, Joshua; Patlamazoglou, Lefteris; Berger, Emily
Abstract: Objective: This project sought to characterize levels of distress in Australian tertiary education students during the COVID‐19 pandemic. Methods: Advertisements were placed on multiple participant recruitment and student run websites associated with various tertiary institutions. Level of overall distress was assessed with the K‐10 so that comparisons could be made with previous research. A total of 1072 tertiary education students 18 years or older participated in the study. Results: 70.9% of tertiary education students studying in Australia displayed elevated levels of psychological distress during the pandemic, with 23.01% of the sample reporting extreme levels of distress. Conclusions: More tertiary education students experienced severe distress during the COVID‐19 pandemic than adults in the general population, as well as before the pandemic. Implications: Services are needed to help tertiary education students cope with elevated levels of distress associated during the COVID‐19 pandemic.